MANAJEMEN PROTEKSI KEBAKARAN DI KOTA PEKANBARU TAHUN 2015-2017 - Abdullah, Risqan; Tinov, M. Y. Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract            The research is motivated by issuance Regulation of the Minister of Public Works No. 20/PRT/M/2009 Regarding Guidelines for Fire Protection Technical Management in Cities. In implementing fire protection management for region that do not yet have specific regulation governing fire protection management, then the implementation of fire protection management in the region is implemented according Regulation of the Minister of Public Works No. 20/PRT/M/2009. Formulation of the problem in this research is how is the implementation of fire protection management in Pekanbaru City in 2015-2017 and what are inhibiting factors for the implementation of fire protection management in Pekanbaru City in 2015-2017.The purpose of this research is to find out implementation of fire protection management in Pekanbaru City in 2015-2017 and describe the inhibiting factors for the implementation of fire protection management in Pekanbaru City in 2015-2017. The method used in this research is descriptive research with qualitative approach method. The type of research data is primary data and secondary data. Data collection techniques in this study are interviews and documentation. Technical analysis of data used is descriptive qualitative data analysis.         The results of research indicate that the implementation of fire protection management in Pekanbaru City in 2015-2017 regulated in Regulation of the Minister of Public Works No. 20/PRT/M/2009 has not been run in accordance with the contents of the regulations that should be the guidance of policy implementation by Badan Penanggulangan Bencana dan Pemadam Kebakaran Pekanbaru city. The inhibiting factors in the implementation fire protection management is facilities and infrastructure are limited, deficient human resources, resistant situation and socialization has not been done optimally. The right solution to overcome these problems is increased human resources, budget, socialization activities by Pekanbaru City Government, BPBPK and Society in more responsive to fire problems.                 Keywords : Implementation, Fire Protection Management, Fire Prevention.